2020
DOI: 10.1183/13993003.01747-2019
|View full text |Cite
|
Sign up to set email alerts
|

Physiological predictors of survival in patients with sarcoidosis-associated pulmonary hypertension: results from an international registry

Abstract: IntroductionSarcoidosis-associated pulmonary hypertension (SAPH) is associated with reduced survival in single-centre studies. The international Registry for SAPH (ReSAPH) with long-term follow-up was established to enrich our knowledge of this complication of sarcoidosis. This analysis aims to elucidate factors associated with reduced transplant-free survival in SAPH patients.MethodsReSAPH contains prospectively collected outcomes of SAPH patients since the time of registry enrolment. Information analysed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 38 publications
6
90
4
Order By: Relevance
“…Previous studies in patients with various types of ILD have shown that the parameters obtained from the 6MWT are important physiological markers associated with increased mortality. [ 31 40 41 42 ] In agreement with previous studies, we found that a 6MWD <300 m was significantly associated with reduced survival, highlighting the importance of the 6MWT as a surrogate marker of disease severity in pSS-ILD patients. In univariate Cox regression analysis, a number of factors were associated with the survival of patients with pSS-ILD; however, in multivariate analysis, we found that male sex, UIP pattern, and a reduced percent predicted FVC were the only independent predictors of increased mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in patients with various types of ILD have shown that the parameters obtained from the 6MWT are important physiological markers associated with increased mortality. [ 31 40 41 42 ] In agreement with previous studies, we found that a 6MWD <300 m was significantly associated with reduced survival, highlighting the importance of the 6MWT as a surrogate marker of disease severity in pSS-ILD patients. In univariate Cox regression analysis, a number of factors were associated with the survival of patients with pSS-ILD; however, in multivariate analysis, we found that male sex, UIP pattern, and a reduced percent predicted FVC were the only independent predictors of increased mortality.…”
Section: Discussionsupporting
confidence: 90%
“…This is problematic as 60% of patients with PH of SCD have elevated left‐sided filling pressures, which are also associated with increased mortality 17 . This phenomenon is similar to what is observed in another form of Group 5 PH, related to sarcoidosis 21 . We utilized the historical definition of PH (mPAP of ≥25 mm Hg) as part of our study design as this was the definition at the time of PDE5‐I utilization.…”
Section: Discussionmentioning
confidence: 82%
“…10 The PH prevalence highly depends on the selected population. PH presents more often in patients with stage IV sarcoidosis, 11,12 and the prevalence increases as the disease proceeds over years. 9 In patients with persistent dyspnea, PH prevalence rises up to 38 to 45%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Identified risk factors for worse prognosis might be Scadding stage IV sarcoidosis, 13 precapillary PH without a postcapillary component (HR: 10.4 compared with 3.14), 13 right atrial pressure >15 mm Hg, 75 DLCO, 12,17 6MWD < 300 m, 12 and right ventricular failure. 88,101 Results on reduced FVC showed various results.…”
Section: Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation